A survey of how and why medical students and junior doctors choose a career in ENT surgery. Issue 11 (17th October 2016) - Bhutta, M; Mandavia, R; Syed, I; Qureshi, A; Hettige, R; Wong, B Y W; Saeed, S; Cartledge, J
Abstract: Objective: To ascertain determinants of an interest in a career in ENT surgery through a survey of medical students and junior doctors. Methods: A survey was administered, comprising Likert scales, forced response and single option questions, and free text responses, at five different courses or events for those interested in a career in ENT. Results: The survey had an 87 per cent response rate; respondents consisted of 43 applicants for national selection, 15 foundation doctors and 23 medical students. The most important factors that encourage ENT as a career included: the variety of operative procedures, work–life balance, inherent interest in this clinical area and inspirational senior role models. Exposure to ENT in undergraduate or post-graduate training is critical in deciding to pursue this specialty. Conclusion: It is important to promote those aspects of ENT surgery that attract people to it, and to argue for greater exposure to ENT during undergraduate and post-graduate training.